2015
DOI: 10.1155/2015/839470
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acupuncture on Cerebral and Muscular Microcirculation: A Systematic Review of Near-Infrared Spectroscopy Studies

Abstract: Acupuncture produces physiological effects via stimulating acupoints, proximal or distal to the region of effect. Near-infrared spectroscopy (NIRS) noninvasively measures tissue-level hemodynamics in real time. We review the literature investigating the effect of acupuncture on muscular and/or cerebral microcirculation. As the basis, we queried PubMed in June 2014 for articles mentioning both acupuncture and NIRS in title/abstract. The reviewed papers investigated either cerebral (n = 11) or muscular hemodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…11 A study using near-infrared spectroscopy (NIRS) to investigate acupuncture stimulation noted that MA and LF EA increased cerebral blood flow. 12 On the other hand, another recent study reported that acupuncture stimulation had no impact on cerebral blood flow 13 ; thus, the data are inconsistent in this regard. In addition, the effect of HF EA on cerebral blood flow and autonomic nervous system function and their potential interactions have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…11 A study using near-infrared spectroscopy (NIRS) to investigate acupuncture stimulation noted that MA and LF EA increased cerebral blood flow. 12 On the other hand, another recent study reported that acupuncture stimulation had no impact on cerebral blood flow 13 ; thus, the data are inconsistent in this regard. In addition, the effect of HF EA on cerebral blood flow and autonomic nervous system function and their potential interactions have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…24 The unique capabilities of NIRS may thus be relevant in monitoring the effect of physical modalities on tissue hemodynamics and oxygenation. [25][26][27][28] The purpose of our study was to investigate the effects of CB on intramuscular perfusion and oxygenation of the lower leg in healthy individuals using noninvasive NIRS. We hypothesized that by altering local hemodynamics, CB would increase the level of intramuscular oxygenated blood volume.…”
mentioning
confidence: 99%
“…Using NIRS, acupuncture intervention on stroke patients showed a significant increase in regional cerebral blood volume or oxyhemoglobin parameters (Li et al, 2011). A systemic review of NIRS studies indicates that acupuncture varies wildly in healthy adults but seems to be more appropriate for disordered populations such as stroke patients (Lo et al, 2015).…”
Section: The Effect Of Acupuncture Treatment On Cerebral Hemodynamicsmentioning
confidence: 99%